Efficacy of green synthesized titanium dioxide nanoparticles in attenuation salt stress in Glycine max plants: modulations in metabolic constituents and cell ultrastructure - Reda E. Abdelhameed; Hegazy S. Hegazy; Hanan Abdalla; Marwa H. Adarosy (BMC Plant Biology, 2025)
Abstract Salinity is among the major abiotic stresses faced by different countries; limiting plant growth, development and yield. This research work was carried out to evaluate the influence of green prepared titanium dioxide nanoparticles (TiO2 NPs) on the growth, metabolic constituents and ultrastructural alterations of soybean (Glycine max L.) plants exposed to salt stress. TiO2 NPs were green synthesized using an aqueous solution of Aloe vera leaf extract and the obtained NPs were identified using several techniques. An in vivo pot experiment was carried out to evaluate the role of foliar sprayed TiO2 NPs (30 ppm) on soybean plants irrigated by six NaCl concentrations (0, 25, 50, 100, 150 and 200 mM). After 15 and 30 days from salt application, growth parameters, photosynthetic pigments, total soluble protein, enzymatic antioxidants and ultrastructural changes were tested for potential tolerance of soybean plants growing under salt stress. Results revealed that increasing salt concentrations induced a significant decrease in shoot length, fresh and dry weights as well as the photosynthetic pigments, these decreases were due to increasing electrolyte leakage of soybean plants. However, application of TiO2 NPs showed improvements in the vegetative growth by increasing its pigments and protein contents. There was a marked increase in the contents of enzymatic antioxidants in salt stressed soybean plants and further accumulation of their contents with TiO2 NPs application. Salt stressed soybean plants showed structural and ultrastructural deformation which was lessened by TiO2 NPs application. Finally, our research demonstrates the role of TiO2 NPs in alleviating salt stress in soybean plants via restoring the antioxidants and cell ultrastructure, highlighting their potential role as a sustainable and eco-friendly strategy.